Entropy-based Cartographic Communication Models: Evolution from Special to General Cartographic Information Theory - LI Zhilin (Acta Geodaetica et Cartographica Sinica, 2016)
Map is a kind of powerful means to help people in understanding the objective world. The key function of map is to transmit spatial information. The measurement of spatial information of maps dates back to 1960s, when the information theory of communication was introduced to the field of cartography. The introduction led to a new branch of cartography, i.e. cartographic information theory. This paper provides a review of the development of cartographic information theory over the past 50 years. Emphasis is on the evolution from the special to the general cartographic information theory.